PROSEDUR PENGGUNAAN ALAT PERLINDUNGAN DIRI DAN BIOSAFETY LEVEL 1 DAN 2 - Amertha Putra Manuaba (DiscoverSys Inc., 2016)
Implementation of the Occupational Health and Safety is one efforts to create a workplace that is safe, healthy, and free from environmental pollution, to reduce occupational accidents and disease, which in turn can improve the efficiency and productivity of labor. This is a descriptive explorative study that discuss about personal protective equipment procedures and biosafety level 1 and 2. Biosafety level is a combination of practice and application of procedures by workers at the laboratory facilities and safety equipment usage when working with dangerous infectious pathogenic agents. Biosafety level term is also used to describe the safe method in handling and managing materials that can infect a laboratory. It can be concluded that biosafety is a discipline in handling and containment system against infectious microorganisms and hazardous biological materials. The principles of biosafety cover the basics of the containment system, including the practice, and the correct laboratory techniques, safety equipment, laboratory facilities to protect workers, the environment and the public from exposure to infectious microorganisms.